On the evolutionary edge of migration as an assortative mating device - Oded Stark; Doris A. Behrens; Yong Wang (University of Warsaw, Centre of Migration Research (CMR), 2008)
In a haystack-type representation of a heterogeneous population that is evolving according to a payoff structure of a prisoner's dilemma game, migration is modeled as a process of 'swapping' individuals between heterogeneous groups of constant size after a random allocation fills the haystacks, but prior to mating. Migration is characterized by two parameters: an exogenous participation-in-migration cost (of search, coordination, movement, and arrangement-making) which measures the migration effort, and an exogenous technology - of coordinating and facilitating movement between populated haystacks and the colonization of currently unpopulated haystacks - which measures the migration intensity. Starting from an initially heterogeneous population that consists of both cooperators and defectors a scenario is postulated under which 'programmed' migration can act as a mechanism that brings about a long-run survival of cooperation.
Keywords: 330; Mobilität; Evolutionäre Spieltheorie; Gefangenendilemma; Soziales Verhalten; Altruismus